Genomic Variation in Dengue Virus Non-Structural Protein 5 (NS5). - Saira Mushtaq; Malik Ihsan Ullah Khan; Muhammad Tahir Khan; Aneeqa Shahid; Rameesha Shafiq; Sarwat Jahan (Aziz Fatimah Medical and Dental College, 2024)
Objective: To identify the most frequently repeated mutations in the NS5 protein in DENV RNA isolated from dengue patients in the province Punjab of Pakistan. Methodology: The study was conducted at Aziz Fatimah Hospital and Allied Hospital Faisalabad during the 2022 dengue outbreak. The temporal sampling method was applied while selecting confirmed dengue patients from both hospitals, and written consent was taken. 120 blood samples were selected in total and after quantification only 23 samples were found fit for whole genome sequencing. Data was uploaded to Torrent Suite Server 4.10 for analysis. Epi Data Analysis, a WHO-developed software program, was used to calculate and summarize mutation frequencies. Excel analysis was used to check for flaws in the data. Results: There were a total of 199 mutations across the entire nonstructural protein 5 (NS5) sequence. NS5 mutations were found in 9 genomic isolates, with Sample (S) 17 having the highest number. Conclusion: The presence of large number of mutations in the structure of NS5 protein may be used in designing specific anti-viral against it, for better management of DENV infection in local settings in future.